Triclocarban enhances short-chain fatty acids production from anaerobic fermentation of waste activated sludge - Wang, Yali; Wang, Dongbo; Liu, Yiwen; Wang, Qilin; Chen, Fei; Yang, Qi; Li, Xiaoming; Zeng, Guangming; Li, Hailong (Water research (Oxford), 2017)
Triclocarban (TCC), one typical antibacterial agent being widely used in various applications, was found to be present in waste activated sludge at significant levels. To date, however, its effect on anaerobic fermentation of sludge has not been investigated. This work therefore aims to fill this knowledge gap. Experimental results showed that when TCC content in sludge increased from 26.7 ± 5.3 to 520.5 ± 12.6 mg per kilogram total suspended solids, the maximum concentration of short-chain fatty acids (SCFA) increased from 32.6 ± 2.5 to 228.2 ± 3.6 (without pH control) and from 211.7 ± 2.4 to 378.3 ± 3.2 mg COD/g VSS (initial pH 10), respectively. The large promotion of acetic acid was found to be the major reason for the enhancement of total SCFA production. Although a significant level of TCC was degraded in the fermentation process, SCFA was neither produced from TCC nor affected by its major intermediates at the relevant levels. It was found that TCC facilitated solubilization, acidogenesis, acetogenesis, and homoacetogenesis processes but inhibited methanogenesis process. Microbial analysis revealed that the increase of TCC increased the microbial community diversity, the abundances of SCFA (especially acetic acid) producers, and the activities of key enzymes relevant to acetic acid production. [Display omitted] •Triclocarban affected SCFA production from anaerobic fermentation of sludge.•A significant level of triclocarban was degraded in the fermentation process.•Triclocarban facilitated solubilization, acidogenesis, acetogenesis, and homoacetogenesis processes.•Triclocarban inhibited methanogenesis process.